India-Pakistan Trade as a Catalyst for Peace process - Mohd Wani, Gull (International Journal of Psychosocial Rehabilitation, 2020)
Historically, the Indian subcontinent was well connected as one integrated economic entity. At the time of partition in 1947, India and Pakistan formed not only one political entity but also one integrated economy. Greater Punjab was one economic entity for centuries before partition bifurcated it between India and Pakistan in 1947. Karachi and Bombay were closely tied sister cities on the sea under the same administrative unit of the Bombay Presidency of the British Raj. Today these regions are all but severed. Earlier, these regions enjoyed trade complementarities and thus interdependence between them. A salient feature of this interdependence is that Pakistan produced raw materials while India processed, thus earning a much higher rate of return. After the 1950s, both countries tried to minimize their trade interdependence. Thereafter, trade volume witnessed a steep decline. The India-Pakistan war of 1965 brought to a halt even the limited amount of trade that was there at the time. This was followed by the Bangladesh War in 1971. Trade on a limited scale resumed only in 1975. In 1996, India and Pakistan became signatories to the South Asia Preferential Trade Agreement, requiring member states to reform tariffs and increase intra-regional trade. In the same year, India granted Pakistan the Most Favored Nation status, and Pakistan decided to expand its positive list (imports from India) to include 596 items. The positive list went on expanding till 2012, when it was finally replaced by a negative list of 1209 items. The present volume of official bilateral trade hovers around US$ 2.3 billion as of 2018. But the bilateral trade balance is heavily in favor of India. Greater India-Pakistan trade will increase the prospects of peace in South Asia.